The cultural dimension of ecology - Saraswati, Baidyanath; Indira Gandhi National Centre for the Arts.; Conference on the Cultural Dimension of Education and Ecology (1995 : New Delhi, India) (New Delhi : Indira Gandhi National Centre for the Arts : D.K. Printworld, 1998)
Papers presented at a Conference on the Cultural Dimension of Education and Ecology, held in New Delhi, on 13-16 October, 1995.
Includes bibliographical references.